A Survey of Computer Usage in Adult Education Programs in Florida Report (Distributed by ERIC Clearinghouse, 1993)
A study was conducted to identify the types and uses of computer hardware and software in adult and community education programs in Florida. Information was gathered through a survey instrument developed for the study and mailed to 100 adult and community education directors and adult literacy center coordinators (92 surveys were returned). The results of the survey showed the following: (1) 63 percent use IBM computers, 52 percent, IBM-compatibles, 51 percent Apple IIs, 34 percent Apple Macintosh, and 21 percent others (respondents reported use of more than one type of computer); (2) 87 percent use 5.25 inch disks, although 67 percent have 3.5 inch disk capabilities; (3) WordPerfect was the most popular software package (63 percent), although Excel, Lotus, Microsoft Word, Microsoft Works, Dbase, and MacWrite were also used; (4) the most significant uses of computers were for instructional programs (79 percent), record keeping (56 percent), correspondence (41 percent), registration (36 percent), desktop publishing (33 percent), and electronic communication (15 percent); (5) less than 25 percent of the students in the programs were using computers; (6) the most significant barrier found by respondents (78 percent) is lack of funding for hardware; (7) 91 percent of the respondents supported the usefulness of computers as instructional tools. The study concluded that computers should be used more widely in adult basic education and that funding should be sought. (The report includes a glossary of 13 computer terms and the survey instrument.) (KC)